A bimetallic composite oxide catalyst for residue oil suspension bed hydrocracking and its preparation
By developing a bimetallic composite oxide catalyst composed of Fe2O3, ZnO and ZnFe2O4, the existing catalysts have solved the problems of low catalytic activity, poor dispersion and high cost in hydrocracking of residual oil, and achieved efficient and economical catalysis Improved results and success rate of mass production.
Patent Information
- Application Number
- CN202310330390.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-03-31
AI Technical Summary
In the hydrocracking of residual oil, existing catalysts have problems such as low catalytic activity, poor dispersion, high cost and low success rate in large-scale production.
Develop a bimetallic composite oxide catalyst, which is prepared by preparation of solution, alkalization, aging and washing, molding and calcining. The catalyst consists of Fe2O3, ZnO and ZnFe2O4, and the molar ratio of Zn and Fe is (1-3): ( 1 to 10), the molar fractions of Fe2O3, ZnO and ZnFe2O4 are 33.3-80%, 1-66.7% and 1-50%, respectively, and the average particle size is 2-50 nm.
The catalytic activity, conversion, selectivity and yield of the catalyst are significantly improved, the carbon deposit rate is reduced, and the problems of low yield and difficult to control performance in large-scale production are solved.
Smart Images

Figure CN116440908B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of petroleum refining, and more specifically, relates to an iron-zinc composite oxide catalyst for preparing light component oils by hydrocracking of residual oil, and its preparation and application. Background Art
[0002] With the increasing heaviness and inferiority of crude oil, and the increasing demand for light oil products, the efficient utilization technology of heavy oil and residual oil has attracted the attention of researchers. The residual oil hydrogenation process is one of the important research directions, which can obtain as many liquid products as possible and remove impurities such as metals and asphaltene. The existing reactor forms include fixed bed, moving bed, boiling bed and suspended bed. Among them, suspended bed hydrogenation has good adaptability to inferior residual oil with high impurity content such as metals, sulfur, nitrogen, asphaltene, etc., and its industrial application is not yet mature. It is very important to develop efficient and inexpensive catalysts suitable for residual oil suspended bed hydrogenation.
[0003] As a petrochemical residue, residual oil is the final product after crude oil distillation. It is often enriched with most of the impurity elements and large molecular weight heavy components in crude oil. Therefore, compared with other distillate oils, residual oil is the most difficult part of crude oil distillation fractions to handle. Residue oil hydrocracking catalysts are divided into two categories: homogeneous catalysts and heterogeneous catalysts. The catalyst is generally added to the feedstock as a catalyst precursor. When it reaches a certain temperature in the reactor, it undergoes in-situ sulfurization to form active species transition metal sulfides (Fe, Co, Zn, Mo, Ni, W, etc.), and then participates in the hydrocracking reaction after reaching the reaction temperature.
[0004] The viscosity of residual oil is large, the residual carbon is high, and the impurity content of metals, asphaltene, etc. is high. Therefore, the reaction performance and dispersibility of the catalyst are the main difficulties in research and development. For example, US4299685 uses the powder after coal combustion as a catalyst, which is low in price and large in addition, but its dispersibility is poor, the hydrogenation effect is weak, and the solid particles contained in the tail oil are difficult to handle. CN101733114A proposes a composite metal oxide catalyst comprising Mo metal and Fe metal, which has strong hydrogenation ability and good dispersibility. The shortcomings of this type of catalyst are: using precious metals as catalyst components, it is expensive, and the tail oil contains more solid particles. For example, CN1133725C proposes a composite catalyst aqueous solution prepared by metal salts such as Fe, Ni, and Mo, which has a higher and stronger cracking activity. The shortcomings of this type of catalyst are: the catalyst aqueous solution has poor solubility with heavy oil and poor dispersion effect. CN1445339A proposes a highly dispersed catalyst, which contains one or more metal compounds such as Cu, Ag, Au, Zn, Hg, etc., and then dispersed into alcohols or alcohol / water mixed solutions to achieve the purpose of uniform dispersion in oil. The disadvantage of this catalyst is that it is necessary to remove water before heavy oil processing to reduce the total reaction pressure or reduce the corrosion of water to the reaction device.
[0005] Directly using oil-soluble catalysts has better dispersibility and catalytic activity. CN1644658A proposes that halogen compounds can be used as additives for heavy oil hydrocracking. Its main catalyst is Mo-DTC (molybdenum dialkyl dithiocarboxylate). Adding acidic compound additives improves the yield of gasoline and diesel. CN1133727C discloses an organic metal catalyst obtained by reacting Mo, W metal with phenylhydroxylamine and its derivatives. The catalyst is well dispersed in heavy oil and can effectively improve the yield of light oil. The advantage of organic metal compounds is that they have good compatibility with heavy oil and high heavy oil conversion rate. However, the disadvantages of the above catalysts are: the organic metal compound has a large molecular weight, a low metal content, a large amount of use when measured by metal content, and high cost.
[0006] Since the 1990s, researchers in this field have been engaged in research on catalysts for hydrogenating residual oil to produce light component oil, and have developed many catalysts, among which iron-based catalysts have the advantages of high catalytic activity and high selectivity of target products. Iron-based catalysts are minerals or residues containing Fe2O3 or FeS2. Fe-based catalysts have the advantages of low price, wide sources, and environmental friendliness, but their catalytic activity is relatively low. Therefore, how to improve the catalytic activity of Fe-based catalysts is a problem that urgently needs to be solved. Most of the prior art uses coprecipitation to produce iron-based catalysts. As is known to people, there are many influencing factors in the process of producing catalysts by coprecipitation, such as changes in stirring speed, concentration of precipitant, concentration after precipitation, and amount of washing water, which may affect the activity and physical strength of the catalyst. In addition, when the existing coprecipitation method is used for the enlarged production of iron-based catalysts, the success rate is often very low, and the possibility of catalyst production failure is very high. The existing coprecipitation method has the problem that it cannot be well used for the actual mass production of catalysts. Therefore, it is necessary to improve it on the basis of the existing coprecipitation method and develop a new method that can produce catalysts with desired performance in large quantities with higher efficiency. Summary of the invention
[0007] In view of the problems existing in the art, the present invention has developed a novel catalyst, which uses metal zinc and iron to construct a composite oxide and is modified into a special iron-based spinel. Compared with the existing catalysts in the art, the catalyst of the present invention exhibits excellent catalytic activity, has a higher conversion rate, selectivity and yield, and a reduced carbon deposition rate. Specifically, the present invention prepares the catalyst through a series of steps such as preparing a solution, alkalizing the solution, aging and washing, molding and roasting, which greatly improves the success rate and yield of the catalyst in the preparation, and eliminates the problems of low yield and difficult to control product performance in the conventional co-precipitation method in the large-scale preparation of the catalyst.
[0008] To achieve the above object, the present invention adopts the following technical solution:
[0009] A bimetallic composite oxide catalyst for residual oil suspension bed hydrocracking, the catalyst is composed of Fe2O3, ZnO and Fe-Zn composite oxide ZnFe2O4, the molar ratio of Zn to Fe in the catalyst is (1-3):(1-10), and the molar fractions of Fe2O3, ZnO and ZnFe2O4 are 33.3-80%, 1-66.7% and 1-50% respectively, the sum of the molar fractions of the three is 100%, and the average particle size of the catalyst is 2-50nm.
[0010] Preferably, the Fe-Zn composite oxide phase belongs to the spinel crystal type. In the prepared nanoscale catalyst, not only different contents of Fe2O3 and ZnO are formed, but also zinc-iron orthospinel (ZnFe2O4) is generated. In this process, the Fe-Zn composite oxide phase satisfies the charge balance.
[0011] A method for preparing a bimetallic composite oxide catalyst for residual oil suspension bed hydrocracking specifically comprises the following steps:
[0012] (1) Add an appropriate amount of inorganic iron source and inorganic zinc source into an appropriate amount of deionized water, and stir and dissolve them using a magnetic stirrer.
[0013] (2) Selecting 25% ammonia water, while keeping the solution obtained in step (1) vigorously stirred, add ammonia water drop by drop to adjust the final pH value of the solution to 9-10.
[0014] (3) The solution prepared in step (2) was allowed to stand at room temperature for 24 hours.
[0015] (4) The precipitate prepared in step (3) is transferred to a suction filtration bottle and washed by suction filtration using deionized water.
[0016] (5) Drying, grinding and calcining the precipitate prepared in step (4) to obtain the bimetallic composite oxide catalyst.
[0017] Preferably, the inorganic iron source used in step (1) is one or more of ferric chloride, ferric sulfate, and ferric nitrate, and the inorganic zinc source is one or more of zinc sulfate and zinc nitrate, and the purity of the two is higher than industrial purity. In the solution prepared in step (1), the concentrations of iron ions and zinc ions are both 0.5-5 mol / L.
[0018] Preferably, in step (1), the magnetic stirring speed is 500-800 r / min and the time is 2-3 h.
[0019] Preferably, the main components of the precipitate prepared in step (4) are Fe(OH)3 and Zn(OH)2.
[0020] Preferably, in step (4), when the inorganic iron source is ferric chloride, it is required to filter and wash until the filtrate is free of chloride ions (detected using a silver nitrate solution).
[0021] Preferably, the calcination temperature of step (5) is 500°C, the calcination time is 3h, the heating process is to heat from room temperature to 300°C at 2°C / min, retain for 60min, then heat to 500°C at 2°C / min and maintain the temperature for 3h to obtain a yellow-brown solid powder.
[0022] Application: The bimetallic composite oxide catalyst is used in the suspended bed hydrocracking of residual oil. Specifically, the bimetallic composite oxide catalyst is used in the suspended bed residual oil hydrogenation process. Based on the residual oil raw material, the amount of catalyst added is 0.5-5wt%, the reaction temperature is 380-430°C, the reaction time is 0.1-5h, the reaction pressure is 6-20MPa, and the hydrogen-oil volume ratio is 500-1500.
[0023] Preferably, based on the residual oil raw material, the amount of catalyst added is 1-3wt%, the reaction time is 0.5-3h, the reaction pressure is 8-18MPa, and the hydrogen-oil volume ratio is 700-1300.
[0024] Preferably, the catalyst is subjected to a sulfurization treatment before the hydrogenation reaction, the sulfurization temperature is 350° C., the initial sulfurization pressure is 14-16 MPa, and the sulfurization time is 3-5 h.
[0025] The advantages of the present invention are as follows:
[0026] (1) The catalyst of the present invention is different from the solid powder catalyst, water-soluble liquid catalyst and oil-soluble liquid catalyst used in the prior art. The catalyst of the present invention is a composite metal oxide bulk catalyst, which contains metal elements of Group IIB and Group VIII with strong hydrogenation performance, and is prepared into ultrafine particles less than 100 nm by chemical methods, which are well dispersed in residual oil. Moreover, since the catalyst is simple to prepare, it has high economic applicability.
[0027] (2) The catalyst of the present invention is a nano-scale solid powder catalyst with strong hydrogenation performance and good dispersibility, and can be well applied to the residual oil suspension bed hydrogenation process. It can process low-quality heavy oil with high impurity content such as metal, sulfur, nitrogen, asphaltene, etc., and the yield of residual oil gas and coke obtained is significantly reduced, and the quality of oil products is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the XRD spectrum of different metal doping ratios of the iron-zinc composite oxide prepared by the present invention;
[0029] Figure 2It is the XRD spectrum of the iron-zinc composite oxide prepared by the present invention at different calcination temperatures;
[0030] Figure 3 It is a TEM image of the iron-zinc composite oxide prepared by the present invention and its particle size distribution histogram. DETAILED DESCRIPTION
[0031] The present invention is described in detail below by way of examples.
[0032] Example 1
[0033] The catalyst FeZn-O-1 was prepared by low-temperature coprecipitation method: 0.2 mol of FeCl3·6H2O and 0.2 mol of ZnSO4·7H2O were weighed according to the amount of 48.2 g of catalyst, and added to 500 mL of deionized water to dissolve, and the ZnSO4·7H2O solution was stirred at room temperature and the FeCl3·6H2O solution was added to generate a yellow clear solution. During 1 hour of full stirring, 25% ammonia water was added dropwise to make the final pH value of the solution about 9.0. Next, it was aged for 24 hours, filtered, washed, dried overnight, and then the sample was taken out and ground. Finally, it was calcined at 500°C for 3 hours and cooled to obtain the catalyst FeZn-O-1. The molar ratio of Zn to Fe in the catalyst was 1:1. The yield of the catalyst and its influencing factors are listed in Table 1. Figure 1 The XRD images of iron-zinc composite oxides with different proportions are shown in Figure 2. Figure 1 It can be found that the composite metal oxide obtained by calcination has a ZnFe2O4 spinel crystal phase, and its peak intensity gradually increases. Table 4 shows the specific surface area and pore structure distribution obtained by N2 physical adsorption of different proportions of iron-zinc composite oxides. It can be found from Table 4 that the specific surface area of the composite metal oxide obtained by calcination first increases and then decreases, and changes from macropores to porous; Figure 3 is the TEM image of FeZn-O-1 and its particle size distribution histogram. Figure 3 It can be found that the composite metal oxide obtained by calcination is aggregated from primary nanoparticles, the size distribution range of the primary nanoparticles is about 7 nm (average particle size), and the size of the aggregated nanoparticles is about 1 μm.
[0034] Example 2
[0035] The catalyst FeZn-O-2 was prepared by low-temperature coprecipitation method: 0.2 mol of FeCl3·6H2O and 0.2 mol of ZnSO4·7H2O were weighed according to the amount of 48.2 g of catalyst, and added to 400 mL of deionized water to dissolve, and the ZnSO4·7H2O solution was stirred at room temperature and the FeCl3·6H2O solution was added to generate a yellow clear solution. During 1 hour of full stirring, 25% ammonia water was added dropwise to make the final pH value of the solution about 9.0. Next, it was aged for 24 hours, filtered, washed, dried overnight, and then the sample was taken out and ground. Finally, it was calcined at 500°C for 3 hours and cooled to obtain the catalyst FeZn-O-2, in which the molar ratio of Zn to Fe was 1:1. The yield of the catalyst and its influencing factors are listed in Table 1.
[0036] Example 3
[0037] The catalyst FeZn-O-3 was prepared by low-temperature coprecipitation method: 0.2 mol of FeCl3·6H2O and 0.2 mol of ZnSO4·7H2O were weighed according to the amount of 48.2 g of catalyst, and added to 500 mL of deionized water to dissolve, and the ZnSO4·7H2O solution was stirred at room temperature and the FeCl3·6H2O solution was added to generate a yellow clear solution. During the 3 h of full stirring, 25% ammonia water was added dropwise to make the final pH value of the solution about 9.0. Next, it was aged for 24 h, filtered, washed, dried overnight, and then the sample was taken out and ground. Finally, it was calcined at 500 ° C for 3 h and cooled to obtain the catalyst FeZn-O-3, in which the molar ratio of Zn to Fe was 1:1. The yield of the catalyst and its influencing factors are listed in Table 1.
[0038] Example 4
[0039] The catalyst FeZn-O-4 was prepared by low-temperature coprecipitation method: 0.05 mol of FeCl3·6H2O and 0.05 mol of ZnSO4·7H2O were weighed according to the amount of 12.05 g of catalyst, and added to 500 mL of deionized water to dissolve, and the ZnSO4·7H2O solution was stirred at room temperature and the FeCl3·6H2O solution was added to generate a yellow clear solution. During the 3 h of full stirring, 25% ammonia water was added dropwise to make the final pH value of the solution about 9.0. Next, it was aged for 24 h, filtered, washed, dried overnight, and then the sample was taken out and ground. Finally, it was calcined at 500 ° C for 3 h and cooled to obtain the catalyst FeZn-O-4, in which the molar ratio of Zn to Fe was 1:1. The yield of the catalyst and its influencing factors are listed in Table 1.
[0040] Example 5
[0041] Catalyst FeZn-O-5 was prepared by low-temperature coprecipitation method: 0.05 mol of FeCl3·6H2O and 0.05 mol of ZnSO4·7H2O were weighed according to the amount of catalyst produced, and added to 500 mL of deionized water to dissolve, respectively. The ZnSO4·7H2O solution was stirred at room temperature and the FeCl3·6H2O solution was added to generate a yellow clear solution. During the 3 h of full stirring, Na2CO3 solution (concentration of 1.5 mol / L) was added dropwise to make the final pH value of the solution about 9.0. Next, it was aged for 24 h, filtered, washed, dried overnight, and then the sample was taken out and ground. Finally, it was calcined at 500 ° C for 3 h and cooled to obtain catalyst FeZn-O-1. The molar ratio of Zn to Fe in the catalyst was 1:1. The yield of the catalyst and its influencing factors are listed in Table 1.
[0042] Table 1 Relationship between the amount of solvent, stirring time, amount of raw materials and catalyst yield
[0043]
[0044]
[0045] Embodiments 6 to 9
[0046] It can be seen from Table 1 that in the low-temperature coprecipitation method, with the increase in the amount of deionized water added as a solvent, the yield of the Fe-Zn composite oxide catalyst increases significantly when other conditions remain unchanged. When the raw material is excessive, the product yield decreases, which may be due to the fact that the generated product is partially dissolved in the solution. However, the yield decreases after the stirring time is too long, which may be due to the fact that the precipitated material dissolves in the alkaline environment formed by ammonia water under continuous stirring. This shows that improving the catalyst preparation method can significantly improve the catalyst yield.
[0047] After comparative analysis in Table 1, the conditions of Example 1 were used to prepare catalysts with different Zn / Fe ratios. The amount of ZnSO4·7H2O was fixed at 0.1 mol, and the molar ratios of Zn and Fe were (0, 1:4, 1:2, 2:1), respectively. They were named catalyst Fe2O3, catalyst Fe4-Zn-O, catalyst Fe2-Zn-O, catalyst Fe 0.5 -Zn-O. Example 6, Example 7, Example 8 and Example 9 are respectively catalyst Fe2O3, catalyst Fe4-Zn-O, catalyst Fe2-Zn-O, catalyst Fe 0.5 - Application of Zn-O in the residual oil suspension bed hydrogenation process. The residual oil conversion rate, gas coke yield, gasoline and diesel yield, liquid yield and product distribution are calculated according to the following formula as the evaluation index of the reaction effect:
[0048] Gas yield (Gas, wt%) = (mass of feedstock oil - total mass of liquid and solid products) / mass of feedstock oil × 100%
[0049] Naphtha yield (Naphtha, wt%) = C5-180°C fraction mass / raw oil mass × 100%
[0050] Diesel yield (wt%) = 180-350°C fraction mass / feedstock oil mass × 100%
[0051] Reduced pressure distillate oil yield (Reduced pressure distillate, wt%) = 350-500°C fraction mass / feedstock oil mass × 100%
[0052] Coke yield (wt%) = coke mass / raw oil mass × 100%
[0053] Conversion (wt%) = (raw oil fraction - product fraction) / raw oil fraction × 100% (where the fraction in the formula is the mass of the fraction > 500°C)
[0054] Catalyst Fe2O3, Catalyst Fe4-Zn-O, Catalyst Fe2-Zn-O, Catalyst Fe 0.5 -Zn-O is vulcanized online during the reaction temperature rise process, that is, carbon disulfide is added to the reaction system as a vulcanizing agent, and the vulcanization temperature is 350°C.
[0055] Reaction conditions: reaction temperature 430°C, initial hydrogen partial pressure 8MPa, reaction pressure range should be 15.5-17.0MPa, residual oil feedstock addition amount is 40g, catalyst addition amount is 0.12g, carbon disulfide 0.95g, stirring speed 600r / min, reaction time 180min, and the reaction results are listed in Table 2.
[0056] The effect of the catalyst on the hydrocracking reaction of residual oil suspension bed is shown in Table 2. When the sample Fe2O3 is used, the gas yield is 15.7wt%, the coke yield is 3.1wt%, and the gasoline and diesel yield is 50.5wt%. After the iron oxide is doped with Zn as a catalyst, the gas and coke in the hydrocracking product are significantly reduced, and the gasoline and diesel yield is also improved to a certain extent. The doping of a small amount of Zn can significantly improve the catalytic activity of the iron oxide catalyst. When the sample FeZn-O-1 (where the Zn / Fe molar ratio is 1:1) is used as a catalyst, the gas and coke yields in the hydrocracking reaction product are only 13.0wt% and 0.7wt%, respectively. Compared with the undoped iron oxide catalyst, the gas and coke yields are reduced by 2.7wt% and 2.4wt%, respectively, and the catalytic activity is greatly improved.
[0057] Examples 9 to 13
[0058] Examples 9-13 are the applications of catalysts ZnFe2O4, Fe2O3 / ZnFe2O4 / ZnO (a physical mixture of three components, in which the molar fractions of Fe2O3, ZnO and ZnFe2O4 are 12.58%, 67.92% and 18.52%, respectively) and FeZn-O-1 in the residue oil suspended bed hydrogenation process.
[0059] The heavy oil feedstock is a kind of atmospheric residue with high asphaltene and metal content. The reaction of treating the residue must be carried out in a specific reactor. The reactor is a 250mL high-pressure stirring device. The catalyst is online sulfurized during the reaction temperature rise process, that is, carbon disulfide is added to the reaction system as a sulfurizing agent, and the sulfurization temperature is 350℃.
[0060] Reaction conditions: reaction temperature 430°C, initial hydrogen partial pressure 8MPa, reaction pressure range should be 15.5-17.0MPa, residual oil feedstock addition amount is 40g, catalyst addition amount is 1.2g, carbon disulfide 0.95g, stirring speed 600r / min, reaction time 180min, and the reaction results are listed in Table 3.
[0061] As can be seen from Table 3, the conversion rates of residual oil are 75.5%, 73.6% and 74.6% respectively, and the conversion rates of coke are 1.2%, 2.1% and 0.7% respectively. In the comparison between Table 1 and Table 3, the iron-zinc composite oxide of Example 1 not only has high yield, but also has controlled catalytic performance, which is conducive to industrialization. In terms of reaction effect, since the activity and selectivity of the catalyst vary with the interaction energy between the catalyst surface and the residual oil components, ZnFe2O4 spinel, as the key structure of hydrocracking residual oil, not only enhances the interaction between ZnO and Fe2O3 and the adsorption capacity of residual oil components, but also accelerates the Fe 3+ The electrons are transferred to Zn 2 + The formation of high-efficiency electron transfer at the interface of the two is conducive to the generation of activated hydrogen, and activated hydrogen is conducive to the hydrogenation reaction and inhibits the catalytic cracking side reaction condensation coke. Therefore, the iron-zinc composite oxide containing spinel has better coke inhibition ability than pure ZnFe2O4 spinel, and its active sites are not easily covered by the generated coke, thereby extending the service life of the catalyst. In addition, since the composite oxide prepared by this method interacts at the molecular level interface to promote the reaction, the catalyst obtained by simple physical mixing of the three components does not have the same liquid yield and gas coke yield.
[0062] Figure 1The changes in the crystal form of the prepared iron-zinc composite oxide before and after metal doping in XRD are described, corresponding to the JCPDS standard cards: Fe2O3 (JCPDS card PDF 33-0664), ZnO (JCPDS card PDF 36-1451), ZnFe2O4 (JCPDS card PDF 65-3111), indicating that ZnO is fully doped into the Fe2O3 lattice to form a spinel structure ZnFe2O4. Figure 2 The changes of different calcination temperatures in the XRD of the prepared iron-zinc composite oxide are described. The catalyst preparation process corresponding to the calcination temperature of 400-700°C is the same as that in Example 1, except that only the calcination temperature is changed. As the calcination temperature increases, the intensity of the newly appeared ZnFe2O4 spinel diffraction pattern fluctuates, among which the characteristic diffraction peaks at 500°C and 700°C are more obvious. However, zinc ferrite will thermally decompose at a temperature higher than 700°C, indicating that 500°C is the best condition for the calcination of the iron-zinc composite oxide, with a stronger ZnFe2O4 diffraction peak and weaker ZnO and Fe2O3 diffraction peaks. Figure 3 Table 4 shows that the average pore size of the prepared iron-zinc composite oxide is about 10-30nm, and the specific surface area changes to varying degrees. According to the current characterization results, FeZn-O-1 has the best catalytic activity, the lowest gas coke yield and a good liquid yield. In this series of iron-zinc oxides, it can be determined from XRD and TEM that zinc-iron spinel (ZnFe2O4) exists. With the increase of ZnO content, the change trend of Fe2O3, ZnO and zinc-iron spinel (ZnFe2O4) ranges from gradually decreasing, first increasing and then basically unchanged, and gradually increasing. The specific values can be referred to Table 5.
[0063] Table 2 Comparison of the effects of catalysts with different Zn / Fe ratios in residual oil
[0064]
[0065] Table 3 Comparison of the effects of iron-zinc composite oxides in residual oil
[0066]
[0067] Table 4 Structural parameters of iron oxide before and after doping with metal Zn
[0068]
[0069] Table 5 shows the distribution of the components in the catalyst
[0070]
[0071] Compared with catalysts with other Fe / Zn ratios, FeZn-O-1 contains not only more ZnFe2O4 but also a certain amount of Fe2O3. The effect of ZnO alone is not good and it acts more as a dispersant and stabilizer. The core of the catalytic activity lies mainly in the interaction between Fe2O3 and ZnFe2O4 under equilibrium, and then a highly active and highly dispersed hydrocracking catalyst is formed through the dispersion of ZnO.
[0072] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. Application of a bimetallic composite oxide catalyst in residual oil suspension bed hydrocracking, characterized in that: The bimetallic composite oxide catalyst is composed of Fe2O3, ZnO and Fe-Zn composite oxide ZnFe2O4, the molar ratio of Zn to Fe in the catalyst is (1-3): (1-10), and the molar fractions of Fe2O3, ZnO and ZnFe2O4 are 33.3-80%, 1-66.7% and 1-50% respectively, and the sum of the molar fractions of the three is 100%, and the average particle size of the catalyst is 2-50nm; The bimetallic composite oxide catalyst is used in a suspended bed residue oil hydrogenation process. Based on the residue oil raw material, the catalyst addition amount is 0.5-5 wt%, the reaction temperature is 380-430 ° C, the reaction time is 0.1-5 h, the reaction pressure is 6-20 MPa, and the hydrogen-oil volume ratio is 500-1500.
2. The use according to claim 1, characterized in that: The Fe-Zn composite oxide phase belongs to the spinel crystal type.
3. The use according to claim 1 or 2, characterized in that: The preparation method of the bimetallic composite oxide catalyst comprises the following steps: (1) Add appropriate amount of inorganic iron source and inorganic zinc source into deionized water and dissolve them by magnetic stirring; (2) Selecting 25% ammonia water, while keeping the solution obtained in step (1) vigorously stirred, add ammonia water drop by drop to adjust the final pH value of the solution to 9-10; (3) The solution prepared in step (2) was allowed to stand at room temperature for 24 h; (4) filtering the precipitate prepared in step (3) and washing it with deionized water; (5) The precipitate prepared in step (4) is dried, ground, and calcined to obtain the bimetallic composite oxide catalyst.
4. The use according to claim 3, characterized in that: The inorganic iron source is one or more of ferric chloride, ferric sulfate and ferric nitrate, and the inorganic zinc source is one or more of zinc sulfate and zinc nitrate.
5. The use according to claim 3, characterized in that: In the solution prepared in step (1), the concentration of iron ions is 0.1-0.5 mol / L, and the concentration of zinc ions is 0.1-0.5 mol / L.
6. The use according to claim 3, characterized in that: The calcination temperature in step (5) is 500°C and the calcination time is 3 h.
7. The use according to claim 1, characterized in that: Based on the residual oil raw material, the amount of catalyst added is 1-3wt%.
8. The use according to claim 1, characterized in that: The reaction time is 0.5-3 h, the reaction pressure is 8-18 MPa, and the hydrogen-to-oil volume ratio is 700-1300.
9. The use according to claim 1, characterized in that: The catalyst is subjected to sulfurization treatment before the hydrogenation reaction. The sulfurization temperature is 350°C, the initial sulfurization pressure is 14-16 MPa, and the sulfurization time is 3-5 h.
Citation Information
Patent Citations
Superfine powder composite metallic oxide catalyst and application thereof
CN101733114A
Residual suspension bed hydrocracking catalyst compounded by several kinds of metal salts
CN1133725C
Hydrocracking catalyst for oil-soluble suspension bed and its prepn
CN1133727C
High decentralization type catalyzer utilized in suspension bed isocracking process
CN1445339A
Hydrocracking of heavy oils / fly ash slurries
US4299685A
Cited By
A method for producing bio-ship fuel and / or bio-aviation coal from biological oil
CN122750385A